Students’ Conceptualization on Citizen Participation in Digital Era: A Mixed Method Research - Trihastuti, Meiwatizal; Dianasari, Dianasari; Retnasari, Lisa; Hidayah, Yayuk; Suryaningsih, Anis (Jurnal Pendidikan Progresif, 2022)
The objective of this research departs from the assumption that citizen participation can maintain democracy in the atmosphere of a country. This study aims to find out how to conceptualize citizen participation in the digital era with a focus on Ahmad Dahlan University students, Yogyakarta. This research uses mixed methods. The location of the study was at Ahmad Dahlan University Yogyakarta. In data collection, the researcher provided online questionnaire by using Google Form and process the data by using SPSS 24 programs. The results of the study revealed that 1) students at Ahmad Dahlan University Yogyakarta had experience as citizen engagement through several individual and group dimensions. 2) Most of the informants stated that the fulfillment of the rights and obligations of citizens needs to be realized in a structured format. Informants revealed that the lack of citizenship literacy can affect the pattern of involvement as citizens. 3) The experience of student participation at Ahmad Dahlan University Yogyakarta is expected to be able to increase civic intelligence, so that the pattern of participation can be associated with several components in the realization of intelligent and good citizens. This study concludes that student participation culture is influenced by civic literacy, information literacy, self-awareness, and participation alone, but there are also some students who are enthusiastic about following the civic context, but some are passive and only participate. The existence of inequality in participation as a citizen is an indication that there is an ongoing task of Civics to nationalize citizens. Keywords: culture of communication, university student, participation, citizen.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202241